A self-reinforcing oxidatively crosslinking waterborne acrylic resin dispersion and a method for preparing the same

CN117247504BActive Publication Date: 2026-10-16ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311357370.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2026-10-16
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

[0003]针对水性丙烯酸树脂分散体或乳液在涂料应用过程中存在的涂膜硬度低、附着力、耐水性、耐盐雾性、耐溶剂性差、储存稳定性和自洁性不足等技术问题,本发明提出一种自增强氧化交联水性丙烯酸树脂分散体及其制备方法,具有储存稳定性、附着力优异,涂膜硬度高,耐水性、耐盐雾性、耐溶剂性良好,VOCs含量低,自洁性良好,成本适中等优点

Benefits of technology

1.本发明制备出的自增强氧化交联型水性丙烯酸树脂分散体及其下游水性丙烯酸树脂涂料产品具有优异的耐水耐盐雾性和耐溶剂性,良好的储存稳定性、涂膜硬度和自洁性,VOCs含量低,符合国家节能减排标准,绿色环保。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117247504B_ABST
    Figure CN117247504B_ABST
Patent Text Reader

Abstract

The application provides a self-reinforced oxidation crosslinking type water-based acrylic resin dispersion and a preparation method thereof, and the dispersion is mainly used for preparing a water-based acrylic resin industrial coating, and the preparation raw materials comprise an epoxy monomer, a high-iodine-value fatty acid, a vinyl hydroxyl monomer, a catalyst, styrene, an initiator, a chain transfer agent, a vinyl hard monomer, a vinyl soft monomer, a hydrophilic monomer, a neutralizing agent, a cosolvent, deionized water and a catalyst drier and the like. The water-based acrylic resin dispersion provided by the application has a particle size Dv(50) less than 75 nm, no precipitation and water separation phenomenon after 2 years of normal temperature storage, and the coating film has excellent adhesion, high hardness, good water resistance, salt fog resistance and stain resistance. The application solves the problems of poor storage stability, low coating film hardness, poor water resistance, salt fog resistance and oil stain resistance of the traditional water-based acrylic industrial coating. Meanwhile, the application has the advantages of green environmental protection, simple production and preparation and the like, and meets the industry development trend.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of polymer material synthesis, and specifically to a self-reinforced oxidative crosslinking waterborne acrylic resin dispersion and its preparation method. Background Technology

[0002] Acrylic resin coatings possess excellent weather resistance, good chemical resistance, and application performance. They are light in color, moderately priced, and widely used in steel structure corrosion protection, mechanical and electrical coatings, and chemical equipment coatings. Currently, oil-based acrylic industrial coatings dominate the market, while water-based acrylic industrial coatings still face several challenges, such as low film hardness, poor storage stability, and poor water and solvent resistance, hindering their further promotion and application. With increasing national environmental protection efforts, water-based acrylic resin coatings are becoming a trend in the coating industry, replacing oil-based coatings. Therefore, it is necessary to provide a high-performance water-based acrylic resin for preparing industrial coatings, which possesses excellent water resistance, salt spray resistance, solvent resistance, good film hardness, storage stability, self-cleaning properties, low VOC content, and moderate cost, making it easily acceptable to users and meeting market application demands. Summary of the Invention

[0003] To address the technical problems of low film hardness, poor adhesion, water resistance, salt spray resistance, solvent resistance, insufficient storage stability, and inadequate self-cleaning properties in the application of waterborne acrylic resin dispersions or emulsions in coatings, this invention proposes a self-reinforced oxidative crosslinking waterborne acrylic resin dispersion and its preparation method. This dispersion offers advantages such as excellent storage stability and adhesion, high film hardness, good water resistance, salt spray resistance, solvent resistance, low VOC content, good self-cleaning properties, and moderate cost.

[0004] To achieve the above objectives, the technical solution of the present invention is implemented as follows: A self-reinforced oxidative crosslinking aqueous acrylic resin dispersion is prepared from the following raw materials in parts by weight: Epoxy monomers: 361-783 parts; High iodine value oleic acid: 104-342 parts; Vinyl hydroxy monomer: 45-165 parts; Catalyst: 22-40 parts; Styrene: 525-990 parts; Initiator: 41-148 parts; Chain transfer agent: 95-349 parts; Vinyl hard monomer: 350-810 parts; Vinyl soft monomer: 315-765 parts; Hydrophilic monomers: 70-175 parts; Neutralizing agent: 115-272 parts; Cosolvent: 835-1930 parts; Deionized water: 1708-6209 parts; Drying agent: 22-70 parts; The solid content of the dispersion is 35%-45%.

[0005] Preferably, the epoxy monomer is E-20 epoxy resin and fluoroglycidyl ether, and the fluoroglycidyl ether is one or a combination of two of 2,2-bisphenol hexafluoropropane diglycidyl ether and octafluorobiphenyl diglycidyl ether.

[0006] Preferably, the high-iodine-value oleic acid is one or a combination of two of linolenic acid, linoleic acid, and arachidonic acid; the vinyl hydroxy monomer is one or a combination of two of hydroxypropyl acrylate, hydroxypropyl methacrylate, and hydroxyethyl acrylate.

[0007] Preferably, the catalyst is tetrabutylammonium bromide; the initiator is one or a combination of azobisisobutyronitrile and azobisisoheptanenitrile; and the chain transfer agent is one or a combination of (1-phenyl)ethyl dithiobenzoate and cumyl dithiobenzoate.

[0008] Preferably, the vinyl hard monomer is one or more combinations of methyl methacrylate, acrylonitrile, methyl acrylate, tert-butyl methacrylate and norbornene methacrylate; the vinyl soft monomer is selected from one or more combinations of n-butyl acrylate, n-butyl methacrylate, isooctyl acrylate and isooctyl methacrylate.

[0009] Preferably, the hydrophilic monomer is one or a combination of two of methacrylic acid, acrylic acid, and butenoic acid; the neutralizing agent is one or a combination of two of N,N-dimethylethanolamine and triethylamine.

[0010] Preferably, the co-solvent is selected from one or a combination of two of propylene glycol methyl ether, propylene glycol butyl ether, and dipropylene glycol methyl ether.

[0011] Preferably, the drying agent is Bochers boc1101.

[0012] Preferably, the preparation method of the self-reinforced oxidative crosslinking aqueous acrylic resin dispersion includes the following steps: (1) Add epoxy monomer, vinyl hydroxy monomer and catalyst to a reactor filled with inert gas at an initial temperature of 80°C, then raise the temperature to 115-160°C, stir at 110-240 rpm for 2-4 hours, then add high iodine value oleic acid and continue the reaction for 2-4 hours. When the acid value drops to below 5 mg KOH / g, cool down to room temperature, then add vinyl hard monomer, vinyl soft monomer, hydrophilic monomer and 50-60% cosolvent and mix evenly to obtain mixture A, which is then discharged for use. (2) Take a new reactor, set the initial temperature to 60-80℃, purge with nitrogen and add the remaining cosolvent and styrene. After the temperature stabilizes, add the initiator and chain transfer agent, set the stirring speed to 130-200 rpm, and react at a constant temperature for 3-4 hours to obtain prepolymer B. (3) Slowly add the mixture A prepared in step (1) to the prepolymer B, control the reaction temperature to 60-80℃, add for 2-5 hours, and continue the reaction for 1.5-3 hours after the addition is completed; then raise the temperature to 90-100℃, continue the reaction for 1 hour, and cool down to 50℃ to obtain polymer C; (4) Continue to slowly add neutralizing agent to the reactor, adjust the stirring speed to 300-500 rpm, and react for 20-30 minutes; then slowly add deionized water and disperse and stir for 1 hour, and finally add drying agent and continue stirring for 30 minutes to obtain self-reinforced oxidative crosslinking waterborne acrylic resin dispersion.

[0013] Preferably, the self-reinforced oxidative crosslinking waterborne acrylic resin dispersion prepared according to the above method has a styrene segment that is a regular homopolymer and an acrylate segment that is a random copolymer; its dispersed particle size Dv(50) < 75 nm.

[0014] The beneficial effects of this invention are: 1. The self-reinforced oxidative crosslinking waterborne acrylic resin dispersion and its downstream waterborne acrylic resin coating products prepared by this invention have excellent water resistance, salt spray resistance and solvent resistance, good storage stability, coating film hardness and self-cleaning properties, low VOC content, meet national energy conservation and emission reduction standards, and are green and environmentally friendly.

[0015] 2. Traditional waterborne acrylic resin coatings mostly use waterborne acrylic emulsions as film-forming substances, which contain a large amount of emulsifiers. These emulsifiers remain in the coating during the film-forming process, leading to a decrease in the water resistance and salt spray resistance of the coating film. Furthermore, coatings prepared from such emulsions have poor storage stability and are prone to demulsification and deterioration. This invention prepares a waterborne acrylic resin through controlled living polymerization. This is achieved by designing the molecular structure of the waterborne acrylic resin and adding acrylic or methacrylic acid monomers containing carboxyl groups during the resin preparation process. This introduces hydrophilic carboxyl groups into the resin molecular chain and achieves water dispersion through salt formation. The final product is a self-emulsifying oxidative crosslinking waterborne acrylic resin dispersion. Because the dispersion is stable without the need for additional emulsifiers during use, it features small particle size and uniform dispersion.

[0016] 3. Simultaneously, this invention employs a living radical polymerization method, designing a structure with ordered styrene hard segments and disordered acrylate segments by controlling the order of monomer addition. During film formation, due to the weak polarity and high glass transition temperature of the styrene hard segments, the styrene structural segments spontaneously aggregate to form styrene microspheres, while the acrylate structure forms a continuous phase. The styrene microspheres dispersed in the acrylate soft segments form physical cross-linking points in the coating film. This effectively improves both the initial and later hardness of the coating while enhancing its mechanical properties.

[0017] 4. The self-reinforced oxidative crosslinking waterborne acrylic resin dispersion prepared by the present invention contains a high-iodine-value oleic acid structure in its acrylate soft segment, which contains a large number of diallyl α-hydrogens. Under the action of a drying agent, it undergoes oxidative crosslinking, further improving the crosslinking density of the coating and improving the overall performance of the coating, such as hardness, water resistance, and salt spray resistance.

[0018] 5. At the same time, by introducing fluorine-containing monomers, this invention reduces the surface energy of the later coating, improves the hydrophobicity and oleophobicity of the coating, and enhances the self-cleaning property of the coating. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 The image shows the infrared spectrum test results of the sample coating prepared in Example 1 of this invention.

[0021] Figure 2 The image shows the GPC test results of the sample prepared in Example 1 of this invention.

[0022] Figure 3 The graph shows the thermogravimetric test results of the sample coating prepared in Example 1 of the present invention.

[0023] Figure 4 The image shows the particle size test results of the sample prepared in Example 1 of this invention.

[0024] Figure 5 The image shows the particle size test results of the sample prepared in Example 3 of this invention.

[0025] Figure 6 The image shows the particle size test results of the sample prepared in Example 5 of this invention. Detailed Implementation

[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0027] Example 1 A self-reinforced oxidative crosslinking aqueous acrylic resin dispersion is prepared from the following components in parts by weight: E-20 epoxy resin: 206 parts; Octafluorobiphenyl diglycidyl ether: 155 parts; Arachidonic acid: 169 parts; Hydroxyethyl acrylate: 64 parts; Tetrabutylammonium bromide: 22 parts; Styrene: 525 parts; Azobisisobutyronitrile: 46 parts; 103 parts of cumyl dithiobenzoate; Methyl methacrylate: 292 parts; Methyl acrylate: 58 parts; n-Butyl acrylate: 315 parts; Methacrylic acid: 44 parts, acrylic acid: 27 parts; Triethylamine: 115 parts; 635 parts of propylene glycol methyl ether; 286 parts of propylene glycol butyl ether; Deionized water: 1708 portions; Bochus 1101 drying agent: 22 parts.

[0028] The preparation process of this self-reinforced oxidative crosslinking aqueous acrylic resin dispersion includes the following steps: (1) Epoxy resin E-20, fluorinated glycidyl ether, vinyl hydroxy monomer and catalyst were added to a reactor filled with inert gas at an initial temperature of 80°C. The temperature was then raised to 115°C, the stirring speed was 240 rpm and the reaction time was 4 hours. Then high iodine value oleic acid was added and the reaction was continued for 4 hours. When the acid value dropped to 2.4 mg KOH / g, the temperature was lowered to room temperature. Then vinyl hard monomer, vinyl soft monomer, hydrophilic monomer and 55% cosolvent were added and mixed evenly to obtain mixture A. The mixture was discharged for use. (2) Take a new reactor, set the initial temperature to 80°C, purge with nitrogen and add the remaining cosolvent and styrene. After the temperature stabilizes, add the initiator and chain transfer agent, set the stirring speed to 130 rpm, and react at a constant temperature for 4 hours to obtain prepolymer B. (3) Slowly add the mixture A prepared in step (1) to the prepolymer B, control the reaction temperature to 60°C, the addition time to 4.6 hours, continue the reaction for 2 hours after the addition is completed, then raise the temperature to 90°C, continue the reaction for 1 hour, and lower the temperature to 50°C to obtain polymer C; (4) Continue to slowly add neutralizing agent to the reactor, adjust the stirring speed to 500 rpm, and react for 30 minutes; then slowly add deionized water and disperse and stir for 1 hour, and finally add drying agent and continue stirring for 20 minutes to obtain an aqueous acrylic resin dispersion with a solid content of 45% of styrene segment homopolymer and acrylate segment random copolymer.

[0029] The self-reinforced oxidative crosslinking aqueous acrylic resin dispersion prepared in Example 1 was subjected to dehydration and drying, and then subjected to Fourier transform infrared spectroscopy (FT-IR). The results are shown in the figure. Figure 1 2927 cm⁻¹ in the infrared spectrum -1 The absorption peak for the CH stretching vibration is located at 1728 cm⁻¹. -1 The absorption peak at 1505 cm⁻¹ is the C=O stretching vibration peak. -1 The absorption peak at 1218 cm⁻¹ corresponds to the C=C skeleton stretching vibration absorption peak on the benzene ring of the epoxy resin, indicating that the epoxy resin used in this invention contains bisphenol A epoxy resin, and that styrene has been successfully polymerized onto the acrylic resin molecular chain; (Figure 1218 cm⁻¹) -1 and 1140cm -1 The absorption peak for the CF bond stretching vibration indicates that the fluorinated monomer was successfully introduced into the resin molecular chain. The prepared oxidative crosslinked aqueous acrylic resin dispersion was subjected to GPC testing, and the results are as follows: Figure 2 As can be seen, the prepared resin has Mn=6203, Mw=8994, and a polydispersity of 1.45, indicating a narrow dispersion, which is consistent with the characteristics of free radical living polymerization. Thermogravimetric analysis of the coating film yielded the following results: Figure 3As shown in the figure, the prepared resin coating film has a thermal decomposition temperature of 380℃, exhibiting good thermal stability. The particle size of the dispersion was measured using a laser particle size analyzer, and the results are shown below. Figure 4 As can be seen from the figure, the prepared dispersion has a uniform particle size distribution, with Dv(90) being 134 nm and Dv(50) being 73 nm.

[0030] Example 2 A self-reinforced oxidative crosslinking aqueous acrylic resin dispersion is prepared from the following components in parts by weight: E-20 epoxy resin: 443 parts; Octafluorobiphenyl diglycidyl ether: 340 parts; Linoleic acid: 342 parts; Hydroxypropyl acrylate: 157 parts; Tetrabutyl ammonium bromide: 39 parts; Styrene: 970 parts; Azobisisobutyronitrile: 146 parts; 349 parts of cumyl dithiobenzoate; Acrylonitrile: 110 parts, methyl methacrylate: 545 parts, tert-butyl methacrylate: 155 parts; 311 parts of n-butyl acrylate, 417 parts of isooctyl acrylate; Butenoic acid: 175 parts; Triethylamine 144 parts; N,N-Dimethylethanolamine: 116 parts; Propylene glycol methyl ether: 1930 parts; Deionized water: 4822 portions; Bochus 1101 drying agent: 71 parts.

[0031] The preparation process of this self-reinforced oxidative crosslinking aqueous acrylic resin dispersion includes the following steps: (1) E-20 epoxy resin, fluorinated glycidyl ether, vinyl hydroxy monomer and catalyst were added to a reactor filled with inert gas at an initial temperature of 80°C. The temperature was then raised to 155°C, the stirring speed was 240 rpm and the reaction time was 2.2 hours. Then high iodine value oleic acid was added and the reaction was continued for 2 hours. When the acid value dropped to 3.6 mg KOH / g, the temperature was lowered to room temperature. Then vinyl hard monomer, vinyl soft monomer, hydrophilic monomer and 50% cosolvent were added and mixed evenly to obtain mixture A. The mixture was discharged for later use. (2) Take a new reactor, set the initial temperature to 80°C, purge with nitrogen and add the remaining cosolvent and styrene. After the temperature stabilizes, add the initiator and chain transfer agent, set the stirring speed to 200 rpm, and react at a constant temperature for 3 hours to obtain prepolymer B; (3) Slowly add the mixture A prepared in step (1) to the prepolymer B, control the reaction temperature to 80°C, control the addition time to 5 hours, and continue the reaction for 1.5 hours after the addition is completed; then raise the temperature to 90°C, continue the reaction for 1 hour, and lower the temperature to 50°C to obtain polymer C; (4) Continue to slowly add neutralizing agent to the reactor, adjust the stirring speed to 340 rpm, and react for 25 minutes; then slowly add deionized water and stir for 1 hour, and finally add drying agent and continue stirring for 30 minutes to obtain a waterborne acrylic resin dispersion with a solid content of 40% styrene segment homopolymer and acrylate segment random copolymer.

[0032] Example 3 A self-reinforced oxidative crosslinking aqueous acrylic resin dispersion is prepared from the following components in parts by weight: E-20 epoxy resin: 312 parts; 2,2-bisphenol hexafluoropropane diglycidyl ether: 155 parts; octafluorobiphenyl diglycidyl ether: 105 parts. Arachidonic acid: 110 parts; Linolenic acid: 113 parts; Hydroxypropyl acrylate: 114 parts; Tetrabutylammonium bromide: 35 parts; Styrene: 762 parts; Azobisisobutyronitrile: 96 parts; (1-Phenyl)ethyl dithiobenzoate: 210 parts; Methyl methacrylate: 620 parts; n-Butyl methacrylate: 632 parts; Acrylic acid: 136 parts; N,N-Dimethylethanolamine: 136 parts; Propylene glycol methyl ether: 1010 parts; dipropylene glycol methyl ether: 450 parts; Deionized water: 4854 portions; Bochus 1101 drying agent: 52 parts.

[0033] The preparation process of this self-reinforced oxidative crosslinking aqueous acrylic resin dispersion includes the following steps: (1) E-20 epoxy resin, fluorinated glycidyl ether, vinyl hydroxy monomer and catalyst were added to a reactor filled with inert gas at an initial temperature of 80°C. The temperature was then raised to 140°C, the stirring speed was 200 rpm and the reaction time was 3 hours. Then high iodine value oleic acid was added and the reaction continued for 3.5 hours. When the acid value dropped to 4.7 mg KOH / g, the temperature was lowered to room temperature. Then vinyl hard monomer, vinyl soft monomer, hydrophilic monomer and 55% cosolvent were added and mixed evenly to obtain mixture A. The mixture was discharged for later use. (2) Take a new reactor, set the initial temperature to 75°C, purge with nitrogen and add the remaining cosolvent and styrene. After the temperature stabilizes, add the initiator and chain transfer agent, set the stirring speed to 130 rpm, and react at a constant temperature for 3.2 hours to obtain prepolymer B; (3) Slowly add the mixture A prepared in (1) to the prepolymer B, control the reaction temperature at 75°C, control the addition time at 3 hours, and continue the reaction for 2 hours after the addition is completed; then raise the temperature to 100°C, continue the reaction for 1 hour, and lower the temperature to 50°C to obtain polymer C; (4) Continue to slowly add neutralizing agent to the reactor, adjust the stirring speed to 500 rpm, and react for 30 minutes; then slowly add deionized water and disperse and stir for 1 hour, and finally add drying agent and continue stirring for 30 minutes to obtain a waterborne acrylic resin dispersion with a solid content of 35% styrene segment homopolymer and acrylate segment random copolymer.

[0034] The particle size of the self-reinforced oxidative crosslinking aqueous acrylic resin dispersion prepared in Example 3 was measured using a laser particle size analyzer. The results are shown in [Figure Number]. Figure 5 As can be seen from the figure, the prepared resin dispersion has a uniform particle size distribution, with Dv(90) being 114 nm and Dv(50) being 68 nm.

[0035] Example 4 A self-reinforced oxidative crosslinking aqueous acrylic resin dispersion is prepared from the following components in parts by weight: E-20 epoxy resin: 228 parts; 2,2-bisphenol hexafluoropropane diglycidyl ether: 330 parts; Linoleic acid: 207 parts; Hydroxypropyl acrylate: 65 parts; Hydroxypropyl methacrylate: 92 parts; Tetrabutylammonium bromide: 30 parts; Styrene: 920 parts; Azobisisobutyronitrile: 47 parts; Azobisisoheptanenitrile: 47 parts; (1-Phenyl)ethyl dithiobenzoate: 163 parts; Methyl methacrylate: 440 parts; Acrylonitrile: 130 parts; Isooctyl acrylate: 610 parts; Methacrylic acid: 110 parts; Triethylamine: 208 parts; Propylene glycol butyl ether: 1437 parts; Deionized water: 4035 parts; Bochus 1101 drying agent: 55 parts.

[0036] The preparation process of this self-reinforced oxidative crosslinking aqueous acrylic resin dispersion includes the following steps: (1) Epoxy resin E-20, fluorinated glycidyl ether, vinyl hydroxy monomer and catalyst were added to a reactor filled with inert gas at an initial temperature of 80°C. The temperature was then raised to 125°C, the stirring speed was 110 rpm and the reaction time was 3.5 hours. Then high iodine value oleic acid was added and the reaction was continued for 3 hours. When the acid value dropped to 4.8 mg KOH / g, the temperature was lowered to room temperature. Then vinyl hard monomer, vinyl soft monomer, hydrophilic monomer and 60% cosolvent were added and mixed evenly to obtain mixture A. The mixture was discharged for later use. (2) Take a new reactor, set the initial temperature to 80°C, purge with nitrogen and add the remaining cosolvent and styrene. After the temperature stabilizes, add the initiator and chain transfer agent, set the stirring speed to 140 rpm, and react at a constant temperature for 3 hours to obtain prepolymer B. (3) Slowly add the mixture A prepared in step (1) to the prepolymer B, control the reaction temperature to 80°C, control the addition time to 2 hours, and continue the reaction for 3 hours after the addition is completed; then raise the temperature to 90°C, continue the reaction for 1 hour, and lower the temperature to 50°C to obtain polymer C; (4) Continue to slowly add neutralizing agent to the reactor, adjust the stirring speed to 300 rpm, and react for 20 minutes; then slowly add deionized water and stir for 1 hour, and finally add drying agent and continue stirring for 30 minutes to obtain a waterborne acrylic resin dispersion with 38% solid content of styrene segment homopolymer and acrylate segment random copolymer.

[0037] Example 5 A self-reinforced oxidative crosslinking aqueous acrylic resin dispersion is prepared from the following components in parts by weight: E-20 epoxy resin: 270 parts; Octafluorobiphenyl diglycidyl ether: 152 parts; Linoleic acid: 277 parts; Hydroxypropyl acrylate: 45 parts; Hydroxyethyl acrylate: 68 parts; Tetrabutylammonium bromide: 34 parts; Styrene: 740 parts; Azobisisobutyronitrile: 95 parts; (1-Phenyl)ethyl dithiobenzoate: 200 parts; Methyl methacrylate: 520, norbornene methacrylate: 100 parts; n-Butyl acrylate: 580 parts; Methacrylic acid: 140 parts; Triethylamine: 184 parts; Dipropylene glycol methyl ether: 1380 parts; Deionized water: 3680 portions; Bochers BOC1101 drying agent: 42 parts.

[0038] The preparation process of this self-reinforced oxidative crosslinking aqueous acrylic resin dispersion includes the following steps: (1) Epoxy resin E-20, fluorinated glycidyl ether, vinyl hydroxyl monomer and catalyst were added to a reactor filled with inert gas at an initial temperature of 80°C. The temperature was then raised to 160°C, the stirring speed was 200 rpm and the reaction time was 2 hours. Then high iodine value oleic acid was added and the reaction was continued for 2 hours. When the acid value dropped to 3.9 mg KOH / g, the temperature was lowered to room temperature. Then vinyl hard monomer, vinyl soft monomer, hydrophilic monomer and 50% cosolvent were added and mixed evenly to obtain mixture A. The mixture was discharged for later use. (2) Take a new reactor, set the initial temperature to 60°C, purge with nitrogen and add the remaining cosolvent and styrene. After the temperature stabilizes, add the initiator and chain transfer agent, set the stirring speed to 130 rpm, and react at a constant temperature for 4 hours to obtain prepolymer B. (3) Slowly add the mixture A prepared in step (1) to the prepolymer B, control the reaction temperature at 60°C, control the addition time at 4.5 hours, and continue the reaction for 3 hours after the addition is completed; then raise the temperature to 95°C, continue the reaction for 1 hour, and lower the temperature to 50°C to obtain polymer C; (4) Continue to slowly add neutralizing agent to the reactor, adjust the stirring speed to 400 rpm, and react for 30 minutes; then slowly add deionized water and disperse and stir for 1 hour, and finally add drying agent and continue stirring for 30 minutes to obtain a waterborne acrylic resin dispersion with 42% solid content of styrene segment homopolymer and acrylate segment random copolymer.

[0039] The particle size of the self-reinforced oxidative crosslinking aqueous acrylic resin dispersion prepared in Example 5 was measured using a laser particle size analyzer. The results are shown in [Figure Number]. Figure 6 As can be seen from the figure, the prepared resin dispersion has a uniform particle size distribution, with Dv(90) being 108 nm and Dv(50) being 62 nm.

[0040] Example 6 A self-reinforced oxidative crosslinking aqueous acrylic resin dispersion is prepared from the following components in parts by weight: E-20 epoxy resin: 580 parts; Octafluorobiphenyl diglycidyl ether: 201 parts; Arachidonic acid: 104 parts; Hydroxypropyl methacrylate: 45 parts; Tetrabutylammonium bromide: 40 parts; Styrene: 990 parts; Azobisisobutyronitrile: 121 parts; cumyl dithiobenzoate: 240 parts; Methyl methacrylate: 462 parts; Methyl acrylate: 258 parts; n-Butyl acrylate: 765 parts; Methacrylic acid: 144 parts; Butenoic acid: 27 parts; Triethylamine: 272 parts; Propylene glycol methyl ether: 450 parts; dipropylene glycol methyl ether: 385 parts; Deionized water: 6209 portions; Bochus 1101 drying agent: 70 parts.

[0041] The preparation process of this self-reinforced oxidative crosslinking aqueous acrylic resin dispersion includes the following steps: (1) Epoxy resin E-20, fluorinated glycidyl ether, vinyl hydroxy monomer and catalyst were added to a reactor filled with inert gas at an initial temperature of 80°C. The temperature was then raised to 115°C, the stirring speed was 240 rpm and the reaction time was 4 hours. Then high iodine value oleic acid was added and the reaction was continued for 4 hours. When the acid value dropped to 2.4 mg KOH / g, the temperature was lowered to room temperature. Then vinyl hard monomer, vinyl soft monomer, hydrophilic monomer and 55% cosolvent were added and mixed evenly to obtain mixture A. The mixture was discharged for use. (2) Take a new reactor, set the initial temperature to 80°C, purge with nitrogen and add the remaining cosolvent and styrene. After the temperature stabilizes, add the initiator and chain transfer agent, set the stirring speed to 130 rpm, and react at a constant temperature for 4 hours to obtain prepolymer B. (3) Slowly add the mixture A prepared in step (1) to the prepolymer B, control the reaction temperature to 60°C, the addition time to 4.6 hours, continue the reaction for 2 hours after the addition is completed, then raise the temperature to 90°C, continue the reaction for 1 hour, and lower the temperature to 50°C to obtain polymer C; (4) Continue to slowly add neutralizing agent to the reactor, adjust the stirring speed to 500 rpm, and react for 20 minutes; then slowly add deionized water and disperse and stir for 1 hour, and finally add drying agent and continue stirring for 30 minutes to obtain an aqueous acrylic resin dispersion with a solid content of 40% styrene segment homopolymer and acrylate segment random copolymer.

[0042] To further illustrate the self-reinforced oxidative crosslinking waterborne acrylic resin dispersion disclosed in this invention, the self-reinforced oxidative crosslinking waterborne acrylic resin dispersions and coating properties prepared in Examples 1-6 were tested accordingly. The test methods are as follows: Storage stability test of dispersion: The self-reinforced oxidative crosslinking waterborne acrylic resin dispersion sample was packed and placed in a 50℃ oven and kept at a constant temperature for 4 weeks. After that, it was taken out and placed at room temperature for observation. If there was no gelation or stratification, the test was passed.

[0043] Dispersion particle size test: The self-reinforced oxidative crosslinking waterborne acrylic resin dispersion was diluted in deionized water, and the particle size and distribution of the dispersion were tested using a laser particle size analyzer.

[0044] Resin coating adhesion test: The adhesion of the dispersion coating prepared in the examples was determined according to the method of GB / T9286-1998.

[0045] Resin coating hardness test: The hardness of the coating film was determined by pencil method according to GB / T6739-2006 standard.

[0046] Resin coating resistance to volatile oils test: According to section 5.4 of GB / T9274-1988. Immerse the sample in solvent oil that meets the requirements of 0004-1990, remove the sample after the specified time, observe after 10 minutes, and evaluate the results according to the provisions of GB / T1766-2008.

[0047] Salt spray resistance test of resin coating: The test adopts GB / T1771-2007 standard to test the resistance of resin coating to neutral salt spray. The coating is considered to pass the test if it does not blister or peel off after 500 hours and slight discoloration is allowed. Water resistance test of resin coating: The water resistance of resin coating is tested according to the method of GB / T1733-1993. The coating is considered to pass the test if it does not bubble or peel off after 500 hours and slight discoloration is allowed.

[0048] Table 1. Test results of coating properties of resin dispersions obtained in Examples 1-6 As shown in Table 1, the self-reinforced oxidative crosslinking waterborne acrylic resin dispersions prepared in Examples 1-6 of this invention have particle sizes Dv(50) < 75 nm and Dv(90) < 135 nm, which are at the nanometer level and uniformly distributed, ensuring the storage stability of the dispersion and downstream coating products. The coating adhesion of the waterborne acrylic resin dispersions prepared by this method all reach grade 0, solving the problem of poor adhesion of traditional waterborne acrylic resin coatings. In terms of water resistance and salt spray resistance, the prepared dispersion coatings all exceed 500 hours, which is superior to industry standards and similar products on the market.

[0049] In the above embodiments, "parts" refers to grams. The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A self-reinforced oxidative crosslinking aqueous acrylic resin dispersion, characterized in that, It is prepared from the following raw materials in parts by weight: Epoxy monomers: 361-783 parts; High iodine value oleic acid: 104-342 parts; Vinyl hydroxy monomer: 45-165 parts; Catalyst: 22-40 parts; Styrene: 525-990 parts; Initiator: 41-148 parts; Chain transfer agent: 95-349 parts; Vinyl hard monomer: 350-810 parts; Vinyl soft monomer: 315-765 parts; Hydrophilic monomers: 70-175 parts; Neutralizing agent: 115-272 parts; Cosolvent: 835-1930 parts; Deionized water: 1708-6209 parts; Drying agent: 22-70 parts; The solid content of the dispersion is 35%-45%; The method for preparing the dispersion includes the following steps: (1) Add epoxy monomer, vinyl hydroxy monomer and catalyst to a reactor filled with inert gas at an initial temperature of 80°C, then raise the temperature to 115-160°C, stir at 110-240 rpm for 2-4 hours, then add high iodine value oleic acid and continue the reaction for 2-4 hours. When the acid value drops to below 5 mg KOH / g, cool down to room temperature, then add vinyl hard monomer, vinyl soft monomer, hydrophilic monomer and 50-60% cosolvent and mix evenly to obtain mixture A, which is then discharged for use. (2) Take a new reactor, set the initial temperature to 60-80℃, purge with nitrogen and add the remaining cosolvent and styrene. After the temperature stabilizes, add the initiator and chain transfer agent, set the stirring speed to 130-200 rpm, and react at a constant temperature for 3-4 hours to obtain prepolymer B. (3) Slowly add the mixture A prepared in step (1) to the prepolymer B at a reaction temperature of 60-80℃ for 2-5 hours. After the addition is complete, continue the reaction for 1.5-3 hours. Then raise the temperature to 90-100℃ and continue the reaction for 1 hour. Then lower the temperature to 50℃ to obtain polymer C. (4) Continue to slowly add neutralizing agent to the reactor, adjust the stirring speed to 300-500 rpm, and react for 20-30 minutes; then slowly add deionized water and disperse and stir for 1 hour, and finally add drying agent and continue stirring and dispersing for 30 minutes to obtain oxidative crosslinking waterborne acrylic resin dispersion.

2. The self-reinforced oxidative crosslinking aqueous acrylic resin dispersion according to claim 1, characterized in that: The epoxy monomer is E-20 epoxy resin and fluorinated glycidyl ether, wherein the fluorinated glycidyl ether is one or a combination of two of 2,2-bisphenol hexafluoropropane diglycidyl ether and octafluorobiphenyl diglycidyl ether.

3. The self-reinforced oxidative crosslinking aqueous acrylic resin dispersion according to claim 1, characterized in that: The high-iodine-value oleic acid is one or a combination of two of linolenic acid, linoleic acid, and arachidonic acid; the vinyl hydroxy monomer is one or a combination of two of hydroxypropyl acrylate, hydroxypropyl methacrylate, and hydroxyethyl acrylate.

4. The self-reinforced oxidative crosslinking aqueous acrylic resin dispersion according to claim 1, characterized in that: The catalyst is tetrabutylammonium bromide; the initiator is one or a combination of azobisisobutyronitrile and azobisisoheptanenitrile; and the chain transfer agent is one or a combination of (1-phenyl)ethyl dithiobenzoate and cumyl dithiobenzoate.

5. The self-reinforced oxidative crosslinking aqueous acrylic resin dispersion according to claim 1, characterized in that: The vinyl hard monomer is one or more of methyl methacrylate, acrylonitrile, methyl acrylate, tert-butyl methacrylate and norbornene methacrylate; the vinyl soft monomer is one or more of n-butyl acrylate, n-butyl methacrylate and isooctyl acrylate and isooctyl methacrylate.

6. The self-reinforced oxidative crosslinking aqueous acrylic resin dispersion according to claim 1, characterized in that: The hydrophilic monomer is one or a combination of two of methacrylic acid, acrylic acid and butenoic acid; the neutralizing agent is one or a combination of two of N,N-dimethylethanolamine and triethylamine.

7. The self-reinforced oxidative crosslinking aqueous acrylic resin dispersion according to claim 1, characterized in that: The co-solvent is one or a combination of two of propylene glycol methyl ether, propylene glycol butyl ether, and dipropylene glycol methyl ether.

8. The self-reinforced oxidative crosslinking aqueous acrylic resin dispersion according to claim 1, characterized in that: The drying agent mentioned is Bochers boc1101.

9. The self-reinforced oxidative crosslinking aqueous acrylic resin dispersion according to any one of claims 1-8, characterized in that, The oxidative crosslinking waterborne acrylic resin dispersion has a styrene segment that is a regular homopolymer and a subsequent acrylate segment that is a random copolymer. Its dispersed particle size Dv50 < 75 nm.

Citation Information

Patent Citations

  • Preparation method of self-crosslinked thermoplastic acrylate resin

    CN101974276A

  • Unsaturated fatty acid modified water-based acrylic resin dispersion body and preparation method thereof

    CN112898479A

  • Light-cured waterborne epoxy resin dispersion and preparation method thereof

    CN115746660A